Comparative physiological and biochemical mechanisms of drought tolerance in three contrasting cultivars of quinoa (Chenopodium quinoa) - Zhang, Yemeng; Yang, Qian; Zhu, Lili; Chen, Zhiguo (Anales del Jardín Botánico de Madrid (1979), 2022)
Quinoa (Chenopodium quinoa Willd.) is a halophytic, pseudocereal crop, which has a richer nutritional value than other major cereals and is highly resistant to multiple abiotic stresses. In this study, the germination characteristics, morphological, physiological and biochemical changes of three contrasting quinoa cultivars under drought stress were compared. The results indicated that ‘Chaidamuhong’ and ‘Gongzha No.3’ showed stronger drought tolerance than ‘Qingli No.1’. This was mainly manifest in seed germination index, activity of antioxidant enzymes, cell membrane damage and morphological changes. We speculate that the increase in the activity of many antioxidant enzymes and the lower stomatal density make ‘Chaidamuhong’ and ‘Gongzha No.3’ superior in release of reactive oxygen species and water retention than ‘Qingli No.1’, thus reducing the degree of cell damage, and improving drought resistance.